Mental health changes and the willingness to take risks - Lu Li; Andreas Richter; Petra Steinorth (The Geneva Risk and Insurance Review, 2021)
Utilizing the longitudinal SOEP data representative of the German population, we find that mental health shocks significantly decrease the willingness to take risks. We also find that mental health improvements increase the willingness to take risks significantly. Our findings are relevant for better understanding the economic decision making of the large number of individuals with mental health issues.
Keywords: 330; Willingness to take risks; Health shock; Health improvement; Mental health; SF-12; I12; D12; D18; D81